Synthesis of Nanocellulose from Coir Pith - Subha, P. V.; Ravindranath, Anita Das (International Coconut Community Journal, 2012)
Coir pith is lignocellulosic in nature and abundantly available by-product of the coir industry. It is a pollutant as it is resistant to biodegradation in the environment. It is mainly composed of cellulose (28%), hemi cellulose (9.5%) and lignin (31%). In this study, cellulose was extracted from the coir pith, and treated generally for the production of nanocellulose. Cellulose is proved to be a versatile material due to its unique chemical structure, which provides a superior platform for several new biomaterials. Nanophase materials are prepared from inorganic materials and hardly any are reported from natural products. When particles are made up to nano size their reactivity increases. FT-IR, TGA, XRD and SEM characterized the extracted cellulose and nanocellulose. The hydrolyzed nanocellulose was found to be the mixed crystalline forms of cellulose I and II. Conversion of this lignocelluloscic biomass to nanocellulose will lead to the preparation of new-nano composites materials for biomedical applications.